Record of a bypass on the oral siphon of Ascidia sydneiensis (Tunicata: Ascidiacea) in a tropical bay from south-eastern Brazil (Ocean and Coastal Research, 2021)
Ascidia sydneiensis Stimpson, 1855 is a solitary ascidian (Order Phlebobranchia) first described in the China Sea and Japan. Recently, it has been recorded in subtropical and tropical regions and is abundant in the Caribbean (Rocha et al., 2005; Worms, 2020). In Brazil, it was first recorded in the São Paulo State (Bjornberg, 1956) and ranges from Ceará to Santa Catarina (Rodrigues, 1962; Rocha and Nasser, 1998; Rocha and Costa, 2005; Rocha and Kremmer, 2005; Rocha et al., 2012). On the coast of Rio de Janeiro State, it was recorded at Ilha Grande Bay, Sepetiba Bay, Arraial do Cabo, and Búzios (Marins et al., 2010; Granthon-Costa et al., 2016).